Persekutuan Meja Makan Sebagai Titik Berangkat Pendidikan Agama Kristen Dalam Keluarga Masa Kini - Ujung, Daniel Pangihutan (JURNAL DIAKONIA, 2024)
Fellowship is one aspect of Christian life, especially family fellowship. Christian life, especially fellowship in the family. In the family, fellowship can be seen at the dinner table or when a family eats together. Fellowship the dining table can facilitate the family's role as educators, the dining table becomes a means for the family to provide becomes a means for families to provide teaching for their children. The church assigns families to educate their children according to the Christian faith. Through table fellowship families spend time teaching children. This paper aims to remind parents to spend their time in the table fellowship as well as teaching the family members about the Christian faith of family members. The author observes that families often forget their duty in growing their faith. In conducting this research, the author literature method by gathering insights from existing literature, describing the the development of thought in a field.